Inverse opal photonic crystals: synthesis techniques, unique properties, and multifunctional applications - Hamsasew Hankebo Lemago; Imre Miklós Szilágyi (Applied Surface Science Advances)
Inverse opal photonic crystals (IOPCs) are highly ordered, porous nanostructures with unique optical, electronic, and mechanical properties, making them valuable for photonics, catalysis, and biosensing applications. This review explores the synthesis methods of IOPCs, including self-assembly, chemical vapor deposition, sol-gel, atomic layer deposition, and electrodeposition, emphasizing their role in tailoring structural and functional properties. The periodicity of these materials gives rise to photonic band gaps and slow photon effects, enhancing their optical performance. Applications of IOPCs in photocatalysis for dye degradation and water splitting, as well as in biological sensing and energy storage, highlight their potential for advanced technological solutions. The incorporation of plasmonic nanoparticles and heterojunctions into IOPCs greatly enhances light-matter interactions, resulting in previously unobserved efficiency in photocatalytic and sensing applications. Moreover, the compositing of flexible IOPC-based devices is made possible by advancements in low-temperature synthesis methods like plasma-enhanced ALD, increasing the materials' applicability in wearable optoelectronics. Future studies will focus on AI-driven design and computational modelling to optimise photonic band gap structures and improve their performance in a variety of domains. This paper provides a comprehensive overview of the fabrication strategies, fundamental properties, and emerging applications of IOPCs, demonstrating their significance in next-generation materials science and engineering.